Indian Trainee Teachers’ Perceptions of 21st Century Skills - Kundu, Arnab; Bej, Dr. Tripti; Dey, Dr. Kedar Nath (Voices of Teachers and Teacher Educators, 2020)
National Curriculum Framework for Teacher Education (NCFTE) provided a meaningful pathway to develop ‘reflective teachers’, creating a cadre of confident, effective and efficacious teachers for 21st century’s fast changing Indian society who can teach effectively in diverse classrooms and for this to happen 21st century skills need to be focussed. This study sought to investigate the Indian trainee teachers’ perception of those skills, to what extent these skills were integrated in Indian teacher education programmes and challenges against this integration. A survey was administered following descriptive method within ex-post-facto research design among 500 final year trainee teachers from 50 teachers’ training colleges stratified random sampling technique. Data were analysed descriptively and inferentially. The findings revealed that few such skills were partially integrated while few others were poorly integrated. Significant differences were found in ingestion of these skills between trainees’ of private and government teacher training colleges. The study also noted the challenges in integrating these skills that will provide valuable reference for teacher education curriculum planning and implementation with a view of providing a holistic educational experience among trainee teachers across the country.